Effects of Short and Long Range Correlations on the Charge Densities and Radii of Ca Nuclei - Lalazissis, G. A.; Massen, S. E. (HNPS Advances in Nuclear Physics, 2019)
The experimental data for the charge (proton) density differences of the even Ca nuclei is analyzed by means of a simple phenomenological model where the effects of certain type short and long range correlations have been accounted. Short range correlations are approximated through the Jastrow type correlation function while for long range correlations the fluctuations of the nuclear surface are considered. The analysis shows that the combined effects of these correlations lead to a better description of the experimental charge (proton) density differences. Moreover, the calculated charge mean square radii of the even Ca nuclei exhibit a parabolic behaviour and compare well with the experimental isotope shifts from the laser spectroscopy measurements.